Application of mixed reality navigation technology in primary brainstem hemorrhage puncture and drainage surgery: a case series and literature review - Tang, Xiaoyong; Wang, Yanglingxi; Tang, Guoqiang; Wang, Yi; Xiong, Weiming; Liu, Yang; Deng, Yongbing; Chen, Peng (Frontiers in Physics, 2024)
The mortality rate of primary brainstem hemorrhage (PBH) is high, and the optimal treatment of PBH is controversial. We used mixed reality navigation technology (MRNT) to perform brainstem hematoma puncture and drainage surgery in seven patients with PBH. We shared practical experience to verify the feasibility and safety of the technology.We introduced the surgical procedure of brainstem hematoma puncture and drainage surgery with MRNT. From January 2021 to October 2022, we applied the technology to seven patients. We collected their clinical and radiographic indicators, including demographic indicators, preoperative and postoperative hematoma volume, hematoma evacuation rate, operation time, blood loss, deviation of the drainage tube target, depth of implantable drainage tube, postoperative complications, preoperative and 1-month postoperative GCS, etc.Result: Among seven patients, with an average age of 56.71±12.63 years, all had underlying diseases of hypertension and exhibited disturbances of consciousness. The average evacuation rate of hematoma was 50.39±7.71%. The average operation time was 82.14±15.74 min, the average deviation of the drainage tube target was 4.58±0.72 mm, and the average depth of the implantable drainage tube was 62.73±0.94 mm. Among all seven patients, four patients underwent EVD first. There were no intraoperative deaths, and there was no complication after surgery in seven patients.The 1-month postoperative GCS was improved compared to the preoperative GCS.It was feasible and safe to perform brainstem hematoma puncture and drainage surgery by MRNT. The technology could evacuate about half of the hematoma and prevent hematoma injury. The advantages included high precision in dual-plane navigation technology, low cost, an immersive operation experience, etc. Furthermore, improving the matching registration method and performing high-quality prospective clinical research was necessary.